PENINGKATAN KUALITAS PRODUK SAKA GRANOLA MELALUI PENDAMPINGAN VARIASI PRODUK BARU - Daton Balamakin, Virgilius; Roslita Ina Mahala, Maria; C. L Putri, Khatarine; Chanelius Laumay, Petrus; Bekti, Rokhana Dwi (DHARMA BAKTI, 2023)
Saka Granola are produced by KWT in Salam Krajan, Wukirsari Village, Cangkringan Sub-District, Sleman, DIY. The production process is still using very simple tools and the product quality still needs to be improved. This is impact on low number of consumers and marketing is still not widespread. Therefore, the PPK Ormawa team, HIMASTA, Statistics Department, Institut Sains & Teknologi AKPRIND Yogyakarta provided assistance to the program to increase the variety of Saka Granola products. The program is carried out during August-October 2022. The forms of assistance include providing training on how to process cocoa into cocoa powder, training in cooking new food products, assistance in producing new products, and marketing. The new product variations have been accepted and are in demand by consumers. These partners have also been able to innovate to develop chocolate food products, increase production, and market.